Confluent and reticulated papillomatosis (Gougerot-Carteaud). - Chieco, P. (European Journal of Pediatric Dermatology, 2015)
Confluent and reticulated papillomatosis (CRP) or Gougerot-Carteaud syndrome is a macular and papular, hyperkeratotic, characteristically reticulated dermatitis, which affects young women, involving the trunk, neck and upper limbs, especially level with the folds. CRP was described for the first time by Gougerot and Carteaud, who in addition to the reticulated form also described a nummular and a verruciformis variety (4). The involvement of the folds and the response to antibiotics speak in favor of a hyperkeratosis reaction to surface bacterial agents. Clinically, CRP resembles pityriasis versicolor (8), but it differs from the latter for no response to antifungal treatment (3). CRP is also reminiscent of acanthosis nigricans (2), especially on the neck, but it differs from the latter for the more advanced age of onset and the involvement of other sites besides the folds. Clinically, CRP predominantly affects females in the second to third decade of life and involves the midthoracic and interscapular area, but it can spread to the neck, to the inframammary sinus, the axillary and cubital folds. The primary lesion is a hypermelanic flat papule or macule of a few mm in diameter, surmounted by pityriasis desquamation getting much more evident with the scratching, well visible at the periphery of the lesions, but confluent with other lesions at the center; when present, the reticulated distribution of the lesions is highly characteristic. With regard to the therapy, the failure to respond to topical antifungals confirms the diagnosis. The disease responds to various antibiotics (1), especially minocycline (5) prolonged for 3-5 weeks, but relapses are frequent (7). Moreover, topical analogues of vit. D, topical and systemic retinoids with variable doses per day and times of administration were successfully used (6).